Implementation of Electricity Business Competition Framework with Economic Dispatch Direct Method - Hermagasantos Zein; Yusra Sabri; Ali Mashar (Institute of Advanced Engineering and Science, 2012)
Technically, electricity business under competition structure is more complex than that of vertically integrated one. The main prolems here are how to create an applicable competition framework and to solve electric calculations very quickly to obtain an optimal energi pricing, cost of losses, congestion and transportation costs by less than 15 minutes. This paper proposes a competition framework with the electric calculations, where a bilateral contract has been accommodated. Optimal energy price in the paper is calculated based on direct method of economic dispatch to obtain the result very quickly. The proposed method has been simulated to a 4-bus system. The simulation results show that the method works well and complies with the expectation. Therefore, electric power business under competition structure can be well realized by the proposed method. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.849